Prognostic value of tissue inhibitor of metalloproteinase-2 expression in patients with non-small cell lung cancer: a systematic review and meta-analysis. - Lin Zhu; Hong Yu; Shi-Yuan Liu; Xiang-Sheng Xiao; Wei-Hua Dong; Yi-Nan Chen; Wei Xu; Tong Zhu (PLoS ONE)
Background and objectives Tissue inhibitor of metalloproteinase-2 (TIMP-2) is a small secretory glycoprotein with anti-matrix metalloproteinase activity. Data on the value of TIMP-2 as a prognostic factor in non-small cell lung cancer (NSCLC) are discordant and remain controversial. A systematic review and meta-analysis was performed to explore this issue. Methods We identified the relevant literature by searching the PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure, SinoMed, and Wanfang Data databases (search terms: "non-small cell lung cancer" or "NSCLC" or "Lung Carcinoma, Non-Small-Cell", "Tissue Inhibitor of Metalloproteinase-2" or "TIMP-2", and "prognosis" or "prognostic" or "survive") for updates prior to March 1, 2014. The pooled hazard ratio (HR) of overall survival with a 95% confidence interval (95% CI) was used to evaluate the strength of the association between positive TIMP-2 expression and survival in patients with NSCLC. Results We included 12 studies in our systematic review; five studies involving 399 patients with NSCLC were meta-analyzed. The pooled HR of all included patients was 0.57 (95% CI: 0.43-0.77), and the HRs of subgroup analysis according to stage (I-IV), testing method (immunohistochemistry) and high TIMP-2 expression percentage (<50%) were 0.63 (95% CI: 0.43-0.92), 0.55 (95% CI: 0.41-0.74), and 0.50 (95% CI: 0.28-0.88), respectively. These data suggested that high TIMP-2 expression is associated with favorable prognosis in NSCLC. The meta-analysis did not reveal heterogeneity or publication bias. Conclusions TIMP-2 expression indicates favorable prognosis in patients with NSCLC; as a protective factor, it could help predict outcome and may guide clinical therapy in the future.